Microbial ecology : - Barton, Larry (Wiley-Blackwell, 2011)
This book covers the ecological activities of microbes in the biosphere with an emphasis on microbial interactions within their environments and communities In thirteen concise and timely chapters, Microbial Ecology presents a broad overview of this rapidly growing field, explaining the basic principles in an easy-to-follow manner. Using an integrative approach, it comprehensively covers traditional issues in ecology as well as cutting-edge content at the intersection of ecology, microbiology, environmental science and engineering, and molecular biology.